KEBUGARAN FISIK SISWA RETARDASI MENTAL RINGAN SEKOLAH DASAR LUAR BIASA KUNCUP BUNGA DENPASAR LEBIH TINGGI SESUDAH MELAKUKAN PELATIHAN SENAM PINGUIN DARI PADA SENAM RIA ANAK INDONESIA - Eka Jaya, I Putu; Karmaya, Nyoman Mangku; Jawi, Made; Weta, Wayan; Ngurah, Ida Bagus; Sagung Sawitri, Anak Agung (Sport and Fitness Journal, 2018)
Physical fitness is ability to perform the activity or activities without feeling tired excessively. Physical fitness associated with a person`s organs to carry out its tasks properly every day without experiencing significant fatigue. In a child’s mental retardation with a les mobile lifestyle that will affect his physical fitness. The purpose of this study to determine which type of gymnastic exercise better to the physical fitness on the students in Sekolah Dasar Luar Biasa Kuncup Bunga Denpasar.This research used experimental method using Randomized study Pre and Post Test Group Design. The subjects in this study were students in Sekolah Dasar Luar Biasa Kuncup Bunga Denpasar. There were 18 students which is divided into two groups: group-1 is senam penguins and group-2 is senam ria anak Indonesia. Data were obtained after a six-week training analyzed by paired t-test and unpaired t-test.The results of physical fitness test before training with Senam Penguins was 23.39 ± 1.69 and the test results after the training was 27.87 ± 3.28. the physical fitness test in group-2 before training with Senam Ria anak Indonesia was 22.69 ± 1.76 and the results after training was 24.64 ± 2.11. Paired t-test in both group before and after training showed significant differences after training in group-1 and group-2 with a value of p > 0.05 with an increase in physical fitness test results of (19.15) in group-1 and (8.64) in group-2. The percentage increase physical fitness test results of group-1 with senam penguins is higher than those in group-2 with senam ria anak Indonesia.So we can conclude that the training of senam penguin in Sekolah Dasar Luar Biasa Kuncup Bunga Denpasar improved the physical fitness test results higher than senam ria anak Indonesia.